2022
DOI: 10.1021/acschemneuro.2c00565
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Clinical Features with Plasma and Multi-modal Neuroimaging Biomarkers to Diagnose Mild Cognitive Impairment in Early Drug-Naive Parkinson’s Disease

Abstract: The pathogenesis of cognitive impairment in Parkinson's disease (PD) patients remains unclear, and there is no ideal diagnostic tool available at present. We assessed integrated clinical features with plasma and multi-modal neuroimaging biomarkers to identify mild cognitive impairment (MCI) in early drug-naive PD patients. 49 early drug-naive PD patients, including 26 with MCI (PD-MCI) and 23 with normal cognition (PD-NC), and 20 controls were recruited. Plasma markers [α-synuclein, betaamyloid 1-40 (Aβ40), be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 60 publications
0
5
0
Order By: Relevance
“…The anterior cingulate and paracingulate gyri (ACG) are mainly involved in cognitive and affective regulation, which has been implicated in cognitive impairment and depression 32–34 . Wang et al 33 found increased FC between the right hippocampal formation and the ACG.L in PD patients with mild cognitive impairment compared to those without mild cognitive impairment. However, Feng et al 34 discovered reduced FC of the ACG in Alzheimer's disease.…”
Section: Discussionmentioning
confidence: 99%
“…The anterior cingulate and paracingulate gyri (ACG) are mainly involved in cognitive and affective regulation, which has been implicated in cognitive impairment and depression 32–34 . Wang et al 33 found increased FC between the right hippocampal formation and the ACG.L in PD patients with mild cognitive impairment compared to those without mild cognitive impairment. However, Feng et al 34 discovered reduced FC of the ACG in Alzheimer's disease.…”
Section: Discussionmentioning
confidence: 99%
“…145,147,[149][150][151][152][153][154] Neuroimaging biomarkers: (i) Dopamine transporter (DAT) imaging with single-photon emission computed tomography (SPECT) or positron emission tomography (PET) can assess presynaptic dopaminergic function and differentiate PD from other parkinsonian syndromes; (ii) Functional MRI (fMRI) can evaluate changes in brain activity and connectivity patterns associated with PD, providing insights into disease pathophysiology and compensatory mechanisms; (iii) Structural MRI techniques, such as volumetric analysis and diffusion tensor imaging (DTI), can detect changes in brain morphology, white matter integrity, and gray matter density associated with PD. 45,145,[155][156][157] Cerebrospinal fluid (CSF) biomarkers: (i) Measurement of α-Synuclein levels or specific αsynuclein species (e.g., oligomeric forms) in CSF may reflect underlying pathology and serve as a diagnostic or prognostic biomarker for PD; (ii) Elevated levels of Tau and phosphorylated Tau (p-Tau) in CSF have been reported in PD patients and may indicate neurodegeneration and tau pathology. 151,153,[158][159][160] Blood-based biomarkers: (i) Blood-based assays for α-Synuclein levels and post-translational modifications are under investigation as potential biomarkers for PD.…”
Section: Biomarkers For Parkinson's Diseasementioning
confidence: 99%
“…However, blood-based αsynuclein assays have been challenging due to low concentrations and high variability; (ii) Biomarkers of neuroinflammation, such as cytokines, chemokines, and inflammatory mediators, have been proposed as potential indicators of disease activity and progression in PD. 153,157,159,161 Genetic biomarkers: (i) Genetic variants associated with PD risk identified through genomewide association studies (GWAS) and next-generation sequencing may serve as genetic biomarkers for disease susceptibility and progression; (ii) Pathogenic monogenic mutations in genes such as SNCA, LRRK2, PARK2, and GBA are associated with familial forms of PD and may serve as biomarkers for genetic testing and personalized risk assessment. 147,[161][162][163] Peripheral biomarkers: (i) Olfactory dysfunction, commonly observed in PD patients, may serve as a peripheral biomarker for early disease detection and monitoring; (ii) Alterations in gut microbiota composition and metabolites have been reported in PD patients and may represent peripheral biomarkers of disease risk and progression.…”
Section: Biomarkers For Parkinson's Diseasementioning
confidence: 99%
“…In addition, fMRI has also been widely utilized to decipher the functional and structural abnormalities causally associated with cognitive deficits in PD patients [3236]. Brain network analysis was an important neuroimaging approach [3741] and has revealed widespread changes of structural and functional networks in PD patients with CI [34, 4244]. Consistently, aberrations in both structural networks and functional network were found to be correlated with cognitive decline in PD patients [25, 34, 45].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, we also showed that global network metrics, such as global efficiency and local efficiency in structural network, partially mediated the age-dependent CI in PD patients [25]. For functional network, it has been shown that increased functional connectivity between left posterior cingulate cortex and left parahippocampal gyrus in default mode network (DMN) was associated with early cognitive decline in PD patients [42]. In addition, functional connectivity between left and right hippocampus in DMN was also associated with global and domain-specific cognitive decline in PD patients [34].…”
Section: Introductionmentioning
confidence: 99%